2013
DOI: 10.1371/journal.pone.0064071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cues Released by an Alien Invasive Aquatic Gastropod Drive Its Invasion Success

Abstract: BackgroundChemical cues provide aquatic organisms with sensory information that guides behavioural responses and thus interactions among themselves, each other and the environment. Chemical cues are considered important for predator avoidance, foraging, larval settlement and broadcast spawning in aquatic environments. However, the significance of their role as drivers of direct interactions between heterospecifics has been largely overlooked.Methodology/Principal FindingsA video camera and a demarcated arena w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
0
45
1
Order By: Relevance
“…was in fact Assimineidae sp.. This false sentinel snail seems to prefer the more saline conditions in the northern parts of St Lucia and has been previously referred to as Coriandria durbanensis or Assiminea durbanensis ( Raw et al 2013 ; Weerts 1993 ). It is clear that Assiminea cf.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…was in fact Assimineidae sp.. This false sentinel snail seems to prefer the more saline conditions in the northern parts of St Lucia and has been previously referred to as Coriandria durbanensis or Assiminea durbanensis ( Raw et al 2013 ; Weerts 1993 ). It is clear that Assiminea cf.…”
Section: Discussionmentioning
confidence: 93%
“…Typically the system experiences sub-decadal alternations of droughts and anomalous wet conditions, at times resulting in severe floods. Recently, the system has undergone a major shift, from a prolonged dry phase during 2002–2011 to flood conditions during 2012–2013, which has resulted in the current predominance of oligohaline conditions through most of its basins ( Raw et al 2013 ; Peer et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown how one such species, Tarebia granifera (Lamarck, 1822), can become extremely abundant, dominate benthic communities (Miranda et al 2011b;Miranda et al 2014a,b) and alter the functioning of environments it has invaded (Miranda et al 2011a;Moslemi et al 2012). Indigenous snail species in particular are being affected and displaced by T. granifera in South Africa (Miranda & Perissinotto 2012;Raw et al 2013). There is evidence that another invasive, Physa acuta Draparnaud, 1805, can displace the snail host of urogenital schistosomiasis and interrupt transmission of the disease (Dobson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…; Raw et al. ). However, fewer recent studies have focused on the function of mucus in land snails other than for use in locomotion or prey tracking (Cook , ; Davis ; Ng et al.…”
mentioning
confidence: 99%